PENGARUH PENGGUNAAN PENDEKATAN TARL BERBANTUAN MEDIA KONKRET PAPAN DADU DIAGRAM TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV DI SDN KEDUNG BADAK 2 - Sintiani, Mitha; Sukmanasa, Elly; Nurul Dhiani, Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The initial reflection made by the researcher was the real demands in the field, regarding mathematics learning based on the concept of presenting bar chart data as a demand for an independent curriculum. Based on the results of observations, there are problems experienced by students, namely low learning outcomes with KKM 75. In learning at school, educators are a very important factor in the learning process. Educators should choose and use appropriate learning strategies to improve student learning outcomes. The goal to be achieved in this research is to improve learning outcomes in class IV bar diagram data presentation material at SDN Kedung Badak 2. The hypothesis in this research is that if learning bar diagrams uses the TaRL approach assisted by concrete dice board diagram media, then students understanding will increase. This improvement was carried out through Classroom Action Research for 2 cycles by taking the research subjects, namely class IV students at SDN Kedung Badak 2. The results of the research showed that using the Teaching at the Right Level (TaRL) approach assisted by concrete media, dice board diagrams, could improve learning outcomes. students in mathematics subjects. This can be seen from the learning outcomes obtained in cycle 1, namely 8 students (32%) obtained scores reaching the KKM, while 17 students (68%) still did not meet the KKM. Improvements were made in the second cycle with the result that 22 students (88%) achieved the KKM score, while 3 students (12%) had not yet reached the KKM. The increase in learning outcomes by 56% is proof that the use of the TaRL approach assisted by concrete diagram dice board media can improve student learning outcomes.